Decolonising human rights: how intellectual property laws result in unequal access to the COVID-19 vaccine. Issue 7 (12th July 2021) - Sekalala, Sharifah; Forman, Lisa; Hodgson, Timothy; Mulumba, Moses; Namyalo-Ganafa, Hadijah; Meier, Benjamin Mason
Abstract : The recent rapid development of COVID-19 vaccines offers hope in addressing the worst pandemic in a hundred years. However, many countries in the Global South face great difficulties in accessing vaccines, partly because of restrictive intellectual property law. These laws exacerbate both global and domestic inequalities and prevent countries from fully realising the right to health for all their people. Commodification of essential medicines, such as vaccines, pushes poorer countries into extreme debt and reproduces national inequalities that discriminate against marginalised groups. This article explains how a decolonial framing of human rights and public health could contribute to addressing this systemic injustice. We envisage a human rights and global health law framework based on solidarity and international cooperation that focuses funding on long-term goals and frees access to medicines from the restrictions of intellectual property law. This would increase domestic vaccine production, acquisition and distribution capabilities in the Global South.